Review of Rhinotora (Diptera, Heleomyzidae) with description of a new species and key to all known heleomyzid species from Brazil - Calhau, Julia; Coelho, Lívia Aguiar; Kawada, Ricardo; Lima, Felipe Varussa De Oliveira; Guillermo-Ferreira, Rhainer (Zootaxa, 2016)
Rhinotora Schiner, 1868, are a rare group of flies, previously including seven species distributed in the Americas, six of them occurring in Brazil. This work aims to provide a taxonomic review for Rhinotora Schiner, with addition of two species in the genus: Rhinotora fonsecai, which is transferred back to its original genus, and R. paschoali sp. nov. New distributional records are presented for R. lopesi and R. travassosi. A key to the all known heleomyzid species recorded from Brazil is provided.